AN APPRAISAL OF MEDIA REPORTAGE OF CHILD RIGHTS IN THE NIGER DELTA REGION: IMPLICATIONS FOR JOURNALISTIC PRACTICES - N. Odedede, Joan (African Journal of Social and Behavioural Sciences, 2024)
This study examines the media coverage of child rights issues in the Niger Delta Region, by assessing the accuracy, depth and ethical considerations of reporting practices. The study adopts the mixed methods approach complementing the quantitative results and interviews with journalists and child rights experts which reveal significant gaps in media reports such as sensationalism, lack of control and inadequate representation of children’s voices. Further research findings revealed that 61 (34.85%) strongly agreed that media reports on child rights are not fair and balanced in terms of representing diverse viewpoints and stakeholders, and 65 (37.14%). Agreed that media reports on child rights prioritize sensationalism over factual accuracy. The interview questions related to the child rights advocate’s responses show that 73 (41.71%) strongly disagreed that media reports do not reflect child rights issues in their work. Moreover, 69 (39.42%) respondents agreed that media reports on children account for 69 (39.42%) that state that media reports on child issues can influence public perceptions of child rights in Nigeria. The study highlights the need for improved journalistic practices, specialized training, ethical guidelines, and collaborative efforts with child rights advocates. The study suggests that enhanced media reporting can shape public perception, influence policy and promote the protection and realization of child rights in the region.